Jamaica: Flagaman Agricultural Information Centre - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Flagaman Agricultural Information Centre was formed by the onion farmers of Flagaman St Elizabeth.